PENGARUH MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA KARTU KATA TERHADAP KETERAMPILAN MENULIS TEKS PUISI SISWA KELAS VIII SMP NEGERI 1 BATUSANGKAR - Dwikafenia, Atifa; Andria Catri Tamsin; Ridha Hasnul Ulya; Muhammad Hafrison (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe students’ skills in writing poetry texts before and after the use of the Project-Based Learning model assisted by Word Card Media, as well as to examine the effect of implementing this model and instructional media on the poetry writing skills of eighth-grade students at SMP N 1 Batusangkar. This study employed a quantitative approach with an experimental method using a one-group pretest-posttest design. The population consisted of all eighth-grade students of SMP N 1 Batusangkar, totaling 253 students, with the sample selected through purposive sampling technique in class VIII.6, consisting of 27 students. The data were in the form of scores from students’ poetry writing tests before and after the implementation of the learning model and media, and the instrument used was a performance test of students’ poetry writing skills. Data analysis was conducted using percentage formulas, mean formulas, prerequisite tests for data analysis, and the t-test. The results of the study indicate three findings: first, before the use of the learning model and media, the average score of students’ poetry writing was 59.84, categorized as fair; second, after the implementation, the average score increased to 73.50, categorized as above fair; and third, the t-test results show that the alternative hypothesis (H1) is accepted because the t-count value is greater than the t-table value (0.64 > 1.93), indicating that students’ poetry writing skills after using the model and media are higher than before. Therefore, it can be concluded that the Project-Based Learning model assisted by Word Card Media has a significant effect on the poetry writing skills of eighth-grade students at SMP N 1 Batusangkar.